2008
DOI: 10.1186/1471-2334-8-113
|View full text |Cite
|
Sign up to set email alerts
|

Rabies trend in China (1990–2007) and post-exposure prophylaxis in the Guangdong province

Abstract: Background: Rabies is a major public-health problem in developing countries such as China. Although the recent re-emergence of human rabies in China was noted in several epidemiological studies, little attention was paid to the reasons behind this phenomenon paralleling the findings of the previous reports. The purpose of this study is thus first to characterize the current trends of human rabies in China from 1990 to 2007, and then to define better recommendations for improving the postexposure prophylaxis (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
68
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 33 publications
2
68
1
Order By: Relevance
“…There was no information about rabies and the risk of animal bite in the current study population. But the findings were consistent with those of the previous studies revealing that the population may not be aware of the risks of animal bites (18,19). Khazaei et al (9) in a similar study reported that distance to the RTC was more than 30 km for 51.3% of the bitten people and 72.5% of them did not receive timely PEP.…”
Section: Discussionsupporting
confidence: 82%
“…There was no information about rabies and the risk of animal bite in the current study population. But the findings were consistent with those of the previous studies revealing that the population may not be aware of the risks of animal bites (18,19). Khazaei et al (9) in a similar study reported that distance to the RTC was more than 30 km for 51.3% of the bitten people and 72.5% of them did not receive timely PEP.…”
Section: Discussionsupporting
confidence: 82%
“…From 1990 to 1996, numbers of cases of human rabies were extremely low due to the nationwide rabies vaccination program (11), although the numbers of rabies cases increased considerably in recent years, due largely to more relaxed dog control measures. Approximately 5,000,000 persons undergo postexposure rabies vaccination annually (11). China accounts for almost two-thirds of the total postexposure prophylaxis (PEP) used in Asia, and the locally produced tissue culture vaccine is safe and relatively inexpensive (7).…”
mentioning
confidence: 99%
“…In 1981, the Semple vaccine was completely replaced by a locally produced tissue cell vaccine (TCV) in China (15). From 1990 to 1996, numbers of cases of human rabies were extremely low due to the nationwide rabies vaccination program (11), although the numbers of rabies cases increased considerably in recent years, due largely to more relaxed dog control measures. Approximately 5,000,000 persons undergo postexposure rabies vaccination annually (11).…”
mentioning
confidence: 99%
“…4 Although declining in recent years, more than 1,400 human deaths were reported in China in the year 2012. [3][4][5][6][7] Following an incubation period of approximately 1-3 months after virus inoculation, the virus travels to the central nervous system, and causes an acute progressive encephalomyelitis followed by coma and death within 1-2 weeks in almost 100% of cases. 8 Although after the onset of clinical symptoms there is no known cure for rabies, timely prophylaxis by vaccination can avert the development of the disease even after exposure to the virus.…”
Section: Introductionmentioning
confidence: 99%
“…Immunogenicity and safety of purified chickembryo cell rabies vaccine under Zagreb 2-1-1 or 5-dose Essen regimen in Chinese children 6 to 17 years old and adults over 50 years: A randomized open-label study…”
mentioning
confidence: 99%